In Vitro Liquid Smoke Potential as Biopesticide on Major Oil Palm Diseases - Setiawan, Wawan; Majid, Muhammad; Putri, Sekar Dian Permata; Tambunan, Van Basten; Wibowo, Cahyo Sri (Universitas Gadjah Mada, 2024)
Liquid smoke is reported as an environmentally friendly pesticide that can effectively manage various crop pathogens. The antimicrobial effect of liquid smoke is believed to be due to its phenol, carbonyl, and organic acid content. The aim of this study was to examine the effect of five commercial liquid smoke at two concentration levels (1% and 2%) on the development of Ganoderma boninense and Curvularia sp. colonies in vitro. This experiment was carried out using a Completely Randomized Design (CRD) with 11 treatments (Control, A1%, B1% C1%, D1%, E1%, A2%, B2%, C2%, D2%, and E2%) and three repetitions. Results showed effects of 11 treatments on test pathogen colonies growth. Liquid smoke types B and C showed the best inhibition against Curvularia sp. and G. boninense. GC-MS analysis revealed that phenol compounds were the dominant compounds, ranging from 24.45% to 85.28%.